Energy business cycles - David Meenagh; Patrick Minford; Olayinka Oyekola (Cardiff University, Cardiff Business School, 2015)
We find that, when estimated, a two sector computable dynamic stochastic general equilibrium open economy model of the U.S. that formally admits energy into the production process can generate plausible parameter values that can be applied to deal with a broad range of economic issues. As a benchmark, we require that the model fits the data for output, real exchange rate, energy use, and consumption: output because it serves as a measure of a country's total income,real exchange rate because it serves as a determinant of a country's relative competitiveness,energy use because it serves as an indicator of special inputs into a country's production process,and consumption because it serves as a yardstick for evaluating a country's standard of living. Finally, we argue that this model, with appropriate extensions, some of which we also propose, can help future modelers to tackle other research questions.
Keywords: E32; D58; F41; C52; Q43; 330; Two sector; US DSGE model; Oil price volatility; Open economy; Indirect inference